IMPLEMENTATION OF STANDARD LANGUAGE WITH SNOWBALL THROWING MODEL TO IMPROVE STUDENT'S SPEAKING SKILLS IN SMA NEGERI 1 TAKALAR - Salsa Nur Rasyidah; Sitti Rabiah; Ihramsari Akidah (Citra Dharma Cindekia, 2022)
This study aims to improve students' speaking skills in using standard language and to find out the results of the snowball throwing learning model in class X students of SMA Negeri 1 Takalar. This research is a class action research carried out in cycles. The subjects in the study were 36 students in class X Mipa 1 at SMA Negeri 1 Takalar. Data collection was carried out by tests and nontes. The implementation stage of the learning steps carried out in cycle I had not been carried out optimally and in cycle II it was carried out as a whole. The results showed that the learning process in cycle I was not optimal with an average value of 72.3%, in contrast to cycle II which experienced a more effective increase with an average value of 86.7%. In addition, there was an increase in the percentage of students who passed based on the speaking ability test, namely from 63.9% of students completing in cycle I to 97.2 in cycle II. In the results of the non-test assessment there was also an increase from the results of the assessment in cycle I to the results in cycle II. Based on the results of this study, it can be concluded that the application of the use of standard language with the snowball throwing learning model to improve students' speaking skills in class X Mipa 1 SMA Negeri 1 Takalar can work very well